A Risky Business: The Tai Ping Insurance Company and Fire Insurance in China, 1928–1937. (28th March 2022) - THAI, PHILIP
Abstract : This paper traces the history of the Chinese fire insurance industry and Tai Ping Insurance, one of the most successful Chinese insurance companies in the early twentieth century. It provides a case study on the "indigenization" of fire insurance in China by retracing how a fledgling firm mastered selling a foreign financial product and managed to win market share in an ostensibly adverse environment. This paper argues that while Tai Ping benefited from the growing embrace of insurance by the Chinese public, its success was ultimately driven by the company's economies of scale, cross-selling synergies, and tight connections to banking. This paper also explores the broader context in which fire insurance operated by examining how the indigenization of insurance in China unfolded, with Chinese insurers like Tai Ping mediating the introduction of a new financial product, the transfer of new institutions, and the diffusion of new knowledge regarding risk. More generally, the history of Tai Ping and the Chinese fire insurance industry addresses a research lacuna in the history of insurance beyond the developed markets in Western Europe and North America, which has typically focused more on the experiences of British and American multinational enterprises and less on that of native companies. By highlighting the degree of institutional convergence and divergence between the Chinese insurance industry and its global counterparts, this paper contributes to a more inclusive history of the internationalization of insurance.